The role of additive technologies in the prototyping issues of design. Issue 7 (12th October 2018) - Carfagni, Monica; Fiorineschi, Lorenzo; Furferi, Rocco; Governi, Lapo; Rotini, Federico
Abstract : Purpose: This paper aims to argue about the involvement of additive technologies (ATs) in the prototyping issues of designing. More precisely, it reviews the literature contributions focused on the different perspectives of prototyping activities for design purposes, searching for both available knowledge and research needs concerning the correct exploitation of ATs. Design/methodology/approach: A two-step literature review has been performed. In the first step, general information has been retrieved about prototyping issues related to design. In the second step, the literature searches were focused on retrieving more detailed information about ATs, concerning each of the main issues identified in the previous step. Extracted information has been analyzed and discussed for understanding the actual coverage of the arguments and for identifying possible research needs. Findings: Four generally valid prototyping issues have been identified in the first step of the literature review. For each of them, available information and current lacks have been identified and discussed about the involvement of AT, allowing to extract six different research hints for future works. Originality/value: This is the first literature review concerning AT-focused contributions that cover the complex and inter-disciplinary issues characterizing prototyping activities in design contexts.